Changes in Global and Nodal Networks in Patients With Unipolar Depression After 3-Week Repeated Transcranial Magnetic Stimulation Treatment - Jang, Kuk-In; Shim, Miseon; Lee, Sangmin; Hwang, Han-Jeong; Chae, Jeong-Ho (Frontiers in Psychiatry, 2019)
Objectives: Repeated transcranial magnetic stimulation (rTMS) therapy has been applied in depressive disorders, but its neurobiological effect has been not well understood. There need to be confirmed changes in cortical source network after treatment. The present study investigated the effect of three-week rTMS therapy on the symptom severity and cortical source network in patients with unipolar depression. Methods: Thirty-five patients with unipolar major depressive disorder participated in the study. Fast frequency (10 Hz) rTMS was applied at the left dorsolateral prefrontal cortex during 3 weeks (5 consecutive weekdays every week). Clinical symptoms were examined using the Hamilton Rating Scale for Depression and Anxiety. The resting state electroencephalography was recorded with 62 scalp channels before and after rTMS treatment. Results: Clinical symptoms significantly improved after rTMS treatment in both the active (p = 0.001) and sham groups (p = 0.002). However, an increased cortical source network in global and nodal levels was observed only in the active group after 3-week treatment. Conclusions: The present study indicates that rTMS treatment leads to improved symptoms in patients with unipolar depression. Furthermore, treatment outcome of real effect was assured in changes of cortical source network.